PENILAIAN KINERJA KARYAWAN PO. LANGGENG JAYA MENGGUNAKAN METODE DECISION TREE DENGAN ALGORITMA ID3 - Wijaya, Laurent Septiani (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Application performance assessment this website is a website application that provides a feature data generation , data storage as well as data calculations used to determine the employee's performance appraisal using ID3 decision tree algorithm ( Iterative Dichotomizer 3 ). Based on the results of tests performed , the application has been successful website provides a feature data generation , data storage as well as data calculations. Making the web application has been successfully generating performance appraisal , as desired by the manufacturer . Key words Decision Tree, Algoritma ID3, Penilaian Kinerja Karyawan, PO.Langgeng Jaya